The World Bank's construction of teachers and their work: A critical analysis. (July 2022) - Pesambili, Joseph C.; Sayed, Yusuf; Stambach, Amy
Abstract: This article examines how World Bank (WB) policy texts discursively constitute teachers and their work as functioning according to a circumscribed set of teaching approaches, while subjugating their reflexive and autonomous professional identities. But neither WB texts nor teacher images within them provide robust accounts of the realities of teachers and their work. What emerges are tropes of policy reforms in teachers and their work arguing for greater regulations underpinned by accountability and performativity regimes. In engendering scepticism of teachers' professional abilities, WB policy discourses reveal an ambivalence about teachers as providers of equitable and quality education: seeing them as a problem while begrudgingly treating them as a solution to the very reforms authorised in the WB policies. Highlights: The WB policy discourse marginalises teachers' professional identities. The WB policy approach promotes narrow scripted professional development and teaching. The WB policy discourse calls for greater teacher accountability and performativity. The WB policy discourse offers a narrow discursive framing of teachers and their work.